Construction de l’identité professionnelle des formateurs d’enseignants : études de cas en formation continue diplômante - Amaury Daele; Annick Rossier; Silvia Sá (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This exploratory study aims at defining the professional identity of teacher educators in a context of certified continuing education and understanding how these educators prepare to exercise this function. Interviews were conducted with internal and external educators at a teacher training institution in French-speaking Switzerland, using the model of teachers' professional identity from Donnay and Charlier (2006) as a reference framework. The content analysis of three out of six interviews, presented in the form of contrasting cases and supplemented by an inter-case analysis, highlights the identity breaks experienced by the educators, particularly in relation to their sense of legitimacy regarding teachers in training, but also in relation to their personal trajectory as trainer within teams of trainers in initial and in-service teacher training. The perspectives relate to the support of teacher trainers in continuing education to define and strengthen their professional identity.